1987
DOI: 10.1002/aja.1001790306
|View full text |Cite
|
Sign up to set email alerts
|

Paracervical ganglia of the female rat: Histochemistry and immunohistochemistry of neurons, SIF cells, and nerve terminals

Abstract: The paracervical ganglia of the female rat were studied to elucidate the variety of neural elements in the ganglia. Light and electron microscopy, histochemistry, and immunohistochemistry were employed to reveal subtypes of neurons; small, intensely fluorescent (SIF) cells; and nerve terminals and to examine the relationships between these elements. On the basis of their histochemical markers, four subtypes of principal neurons were identified: acetylcholinesterase (ACHE)-positive, noradrenergic, neuropeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…This plexus of axons was not obvious in uterine horns stained for TH, although TH staining in other uterine regions was uniformly robust. In the female rat, both the major pelvic ganglion (also called the paracervical ganglion) and the inferior mesenteric ganglion contain sympathetic postganglionic neurons that project to the uterus, and in both ganglia the majority of TH-immunoreactive neurons also contain NPY (Papka et al, 1987(Papka et al, , 1996. Nevertheless, the absence of TH-immunoreactive axons at the circular muscle-endometrium interface suggests that sympathetic axons do not make a major contribution to the circular muscle plexus.…”
Section: Sympathetic Innervation Of the Nonpregnant Rat Uterusmentioning
confidence: 92%
“…This plexus of axons was not obvious in uterine horns stained for TH, although TH staining in other uterine regions was uniformly robust. In the female rat, both the major pelvic ganglion (also called the paracervical ganglion) and the inferior mesenteric ganglion contain sympathetic postganglionic neurons that project to the uterus, and in both ganglia the majority of TH-immunoreactive neurons also contain NPY (Papka et al, 1987(Papka et al, , 1996. Nevertheless, the absence of TH-immunoreactive axons at the circular muscle-endometrium interface suggests that sympathetic axons do not make a major contribution to the circular muscle plexus.…”
Section: Sympathetic Innervation Of the Nonpregnant Rat Uterusmentioning
confidence: 92%
“…The presence in the rat uterus of a substantial contribution of short sympathetic fibres remains controversial. Some authors have reported that one-third to a half of the neurons in the rat paracervical ganglia are noradrenergic (Kanerva et al 1972 ;Inyama et al 1985), whereas only a few or no noradrenergic neurons have been recognised by others (Garfield, 1986 ;Papka et al 1987 ;Hondeau et al 1995Hondeau et al , 1998.…”
Section: mentioning
confidence: 99%
“…The percentage of neurons containing noradrenaline (NA) in pelvic ganglia depends on species and gender and is correlated with a density of adrenergic innervation of genital organs. For example, a rat myometrium exhibits a low number of adrenergic fibres (Adham and Schenk, 1969;Papka et al, 1985), which is correlated with a low number of adrenergic neurons in paracervical ganglia (Papka et al, 1987;Houdeau et al, 1995). The situation is similar in mice (Wanigasekara et al, 2003) and guinea pigs Dhami and Mitchell, 1991;Elfvin et al, 1997).…”
Section: Discussionmentioning
confidence: 69%
“…The available literature reports similar results to the ones described above (Inyama et al, 1985;Morris and Gibbins, 1987;Papka et al, 1995;Majewski, 1997). In the rat PCG VIP-positive neurons constitute one third to one half of all the PCG's neurons (Inyama et al, 1985;Papka et al, 1987), and in a guinea pig's PCG this number is even higher (62-65%; Gu et al, 1984;Morris and Gibbins, 1987). VIP was also found in numerous neurons in the pelvic ganglia of a boar (Kaleczyc, 1997;Kaleczyc et al, 2003) and sow (Majewski, 1997;Wasowicz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%